Penelusuran Bakat dan Minat pada Siswa Kelas XI (Studi Kasus) - Fransiska Susilo (Provitae: Jurnal Psikologi Pendidikan, 2012)
One of the confusions that mostly high-school students encounter related with the academic aspect is the issue of selecting a course. The course which they undertake when they are in high-school is frequently based upon the course which they will later undergo in the university. Therefore, the understanding of aptitude and ability test is necessary to help students answer their confusion of the course in the university level they will take. The result of the aptitude and ability test of the high-school student inthis research shows that she has strong points in several fields. The student herself has made a number of course options which fit her aptitude and ability. Hence, the next step that she carries out is making some alteration to other factors such as the financial condition of the parents and the prediction of work availability in the future. Eventually, her mathematical skills in accordance with the other factors have led her to prioritize the economic accounting as the course she will take in the university.Keywords: high-school student, course, aptitude and ability test